Personality development characteristics of women with anorexia nervosa, their healthy siblings and healthy controls: What prevents and what relates to psychopathology? - Amianto, Federico; Abbate-Daga, Giovanni; Morando, Sara; Sobrero, Cinzia; Fassino, Secondo (Psychiatry research, 2011)
This exploratory study assessed attachment and personality in anorexic women, non-affected siblings, and healthy controls, examining correlations with psychopathology. Thirty-eight anorexic subjects (31 females), thirty-one siblings (22 females), and fifty controls (35 females) participated. Personality development characteristics were assessed using the Attachment Style Questionnaire (ASQ), Temperament and Character Inventory (TCI), Eating Disorders Inventory (EDI-2), Symptom Checklist-90 (SCL-90), and other inventories for clinical assessment of EDs. Both anorexic probands and their siblings described lower maternal care and higher maternal overprotection than did controls. Healthy siblings were more similar to controls, but had lower scores than either controls or affected siblings on preoccupation with relationships (P<0.005) and higher scores than controls on self-transcendence (P<0.015) and obsessive–compulsive traits (P<0.025). Logistic regression indicated that need for approval, persistence, resourcefulness, self-transcendence, state anger, pursuit of thinness, interpersonal distrust, social insecurity, and binge eating differentiated anorexic probands from siblings. The need for approval was related to several psychopathological characteristics. Low preoccupation with relationships, low need for approval, and high self-transcendence may have protected siblings from family and environmental stressors. High need for approval was independently related to psychopathological traits in anorexic siblings. Implications for prevention and treatment are discussed.